Empowerment of Coastal Communities Using Village Funds in Jayabakti Village, Pagimana District, Banggai Regency - Siribun, Salonika; Natsir, Nawawi; Nasrullah, Nasrullah (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to find out community empowerment in the use of Village Funds in Jaya Bakti Village, Pagimana District, Banggai Regency. The research uses qualitative methods to understand the dynamics of community empowerment through the management of Village Funds, allowing researchers to explore the perspectives of participants in depth. Primary data was obtained through interviews with Village Heads, village officials, and community leaders, while secondary data was obtained from documentation and related literature. The data analysis technique follows the Miles and Huberman model, including data reduction, data presentation, and cyclical conclusion drawn. The results of the study show that the bottom-up approach in empowerment has been implemented, but community participation has not been maximized due to limited integration between community groups. Sustainability programs, especially in the agricultural sector, have been running as planned. The use of Village Funds has shown social and economic benefits, although improvements are still needed to achieve equitable participation. In conclusion, the success of community empowerment in the use of Village Funds requires transparency, justice, and continuous cooperation between the village government and the community.